Supportive care needs of multicultural patients with cancer in the United Arab Emirates - Nair, Satish Chandrasekhar (Ecancermedicalscience, 2018)
Despite the high prevalence of cancer in the Middle East, there is limited published data reporting the needs of cancer patients in this region of the world. The purpose of this study is to assess the unmet supportive care needs of oncology patients in the United Arab Emirates (UAE). From December 2014 to December 2016, a cross-sectional survey of cancer patients was conducted at a large tertiary care hospital and an oncology referral centre in the UAE, using a validated Arabic translation of the supportive care needs survey––short form (SCNS-SF34-A), assessing cancer-specific perceived needs across five domains: psychological, health system information, patient care and support, physical and daily living and sexuality. Chi-square test and Pearson’s correlation coefficient were used to assess the association between variables. Participant responses were tabulated as mean ± standard error of the mean (SEM). The response rate was 78% (210/268). Five of the 10 items from the psychological domain constituted the 10 most prevalent unmet moderate or high needs, followed by physical and daily living needs (3.04 ± 0.029, p < 0.001), health system information (3.03 ± 0.02, p < 0.001), patient care and support (2.95 ± 0.24, p < 0.001), with low sexuality needs (1.79 ± 0.08, p < 0.001). Women had significantly higher psychological unmet needs. Cultural differences were noted only in the health system information domain. Improvements in mental health services, development of multidisciplinary cancer care teams, introduction of cancer support groups and fully engaging women in all treatment decisions are feasible and easy to implement interventions that can significantly improve the care and wellbeing of oncology patients in the UAE.